A comparison of the perceived spiritual care provided by nursing staff at the General Nursing Section, Maharaj Nakorn Chiang Mai Hospital - khuansuwan, Issaree; Pintapin, Thanomchit; Wongtan, Weeraphong; Suwanpreda, Rabiap; Nantayana, Kanokwan; Thongphala, Chantana; Sawatdee, Jarunee; Ngnammuangpak, Saharat (Biomedical Sciences and Clinical Medicine, 2016)
The objective of the study is to measure the perception level in spiritual care of the nursing staff at the General Nursing Section, Maharaj Nakorn Chiang Mai Hospital. The comparison of their own perception in spiritual care is also conducted each ward. The methods used in this study include questionnaire in order to determine the perception of the nurses, on spiritual care. Nurses, practical nurses and helpers, a total of 138 staff members, participated in the questionnaire. The validity and reliability of the questionnaire was 0.95 and 0.93 and the statistics used for data analysis were mean and standard deviation. The results of the study showed that the perception level in spiritual care of the nursing staff was high. The perception of the nursing staffs in each ward was at moderate to high levels. In conclusion, the perception level in spiritual care of the nursing staff was high.